1992
DOI: 10.1103/physrevb.45.5710
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and disorder fluctuations in anisotropic superconductingNd1.85Ce0.15

Abstract: The anisotropic vortex transport properties of c-axis-oriented Nd& 85Ceo»Cu04 "superconducting epitaxial films are found consistent with a dislocation-mediated second-order vortex-solid melting transition. The anisotropic critical exponents and the electronic mass ratio are determined from the scaling of the current-voltage characteristics. The nucleation energy of vortex dislocations due to both thermal and disorder fluctuations and its relation to the vortex elastic moduli is inferred from our experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
1
14
2
Order By: Relevance
“…Previous research focused on the quantum critical point thought to occur near optimal doping 7 but there has been very little research on the more well-established vortexglass transition and almost none on the second-order normalsuperconducting transition in zero field. Earlier work on Nd 2−x Ce x CuO 4−y ͑NCCO͒ in a magnetic field reports values for the dynamic and static critical exponents z and for the vortex-glass transition similar to other experiments on the hole-doped cuprates, finding z Ϸ 3,4 and Ϸ 2 , 0.9; 8,9 while work in magnetic fields from 1 mT to 1 T finds a range of exponents z Ϸ 5-9 and Ϸ 0.9-1.8. 10 This wide range of results is similar to results on the hole-doped cuprates.…”
Section: Introductionsupporting
confidence: 75%
“…Previous research focused on the quantum critical point thought to occur near optimal doping 7 but there has been very little research on the more well-established vortexglass transition and almost none on the second-order normalsuperconducting transition in zero field. Earlier work on Nd 2−x Ce x CuO 4−y ͑NCCO͒ in a magnetic field reports values for the dynamic and static critical exponents z and for the vortex-glass transition similar to other experiments on the hole-doped cuprates, finding z Ϸ 3,4 and Ϸ 2 , 0.9; 8,9 while work in magnetic fields from 1 mT to 1 T finds a range of exponents z Ϸ 5-9 and Ϸ 0.9-1.8. 10 This wide range of results is similar to results on the hole-doped cuprates.…”
Section: Introductionsupporting
confidence: 75%
“…32,33 While numerous experiments have been carried out so far using high-T c oxide superconductors ͑HTSC's͒, which have large thermal fluctuations and the extreme type II nature, studies on conventional ͑low-T c ͒ superconductors ͑LTSC's͒ have not been made except for quite limited systems. 34,35 This paper focuses on the possibility of the vortex-glass ͑VG͒ transition in LTSC's.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, for the electron-doped cuprates like Nd 2Ϫx Ce x CuO 4Ϫ␦ previous investigations of the scaling of current-voltage (I-V) characteristics that provided evidence for the existence of the glass transition have been restricted to the low magnetic field region (Hр10 kOe͒. 11,12 In a previous study on Nd 2Ϫx Ce x CuO 4Ϫ␦ single crystals, 13 an interesting anomaly in the temperature dependence of the in-plane electrical resistivity ab (T) was observed at temperatures Tр2 K for crystals with T c р11 K in applied magnetic fields Hʈc . This anomaly resembled reentrant behavior with (T) increasing below Ϸ2 K and then dropping sharply below Ϸ1 K. It was suggested that this behavior could be related to the antiferromagnetic ͑AFM͒ ordering of the Nd 3ϩ ions.…”
Section: Introductionmentioning
confidence: 99%